2004
DOI: 10.1111/j.1432-1033.2004.04050.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane binding of SRP pathway components in the halophilic archaea Haloferax volcanii

Abstract: Across evolution, the signal recognition particle pathway targets extra‐cytoplasmic proteins to membranous translocation sites. Whereas the pathway has been extensively studied in Eukarya and Bacteria, little is known of this system in Archaea. In the following, membrane association of FtsY, the prokaryal signal recognition particle receptor, and SRP54, a central component of the signal recognition particle, was addressed in the halophilic archaea Haloferax volcanii. Purified H. volcanii FtsY, the FtsY C‐termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 53 publications
(80 reference statements)
4
27
2
Order By: Relevance
“…The A domain has been reported as essential for proper targeting of membrane proteins (42); however, more recent in vivo analyses showed that, in E. coli, the N-terminal A-domain was not required for SRP-mediated protein targeting and membrane assembly (43). In contrast, in the halophilic Archaea Haloferax volcanii, the full-length FtsY is essential for the association of Ffh protein with the cell membrane (44). Therefore, the mode of action and requirement of the A domain appears to differ among species.…”
Section: Elimination Of Ftsy Is Similar To Elimination Of Ffhmentioning
confidence: 96%
“…The A domain has been reported as essential for proper targeting of membrane proteins (42); however, more recent in vivo analyses showed that, in E. coli, the N-terminal A-domain was not required for SRP-mediated protein targeting and membrane assembly (43). In contrast, in the halophilic Archaea Haloferax volcanii, the full-length FtsY is essential for the association of Ffh protein with the cell membrane (44). Therefore, the mode of action and requirement of the A domain appears to differ among species.…”
Section: Elimination Of Ftsy Is Similar To Elimination Of Ffhmentioning
confidence: 96%
“…Furthermore, a more complete understanding of the Archaea has proven to have important implications for our understanding of cellular functions conserved in Eukarya and Bacteria (21,34). This has been demonstrated in studies examining archaeal protein translocation via the universally conserved Sec pathway, which is thought to be responsible for the translocation of the majority of proteins into and across the endoplasmic reticular (ER) or cytoplasmic membranes in eukaryotes and prokaryotes, respectively (19,35). Specifically, the notable achievement of the crystal structure of an archaeal Sec translocation pore, the first such structure obtained from any organism, has greatly contributed to the understanding of this universally conserved pore in all organisms (42).…”
mentioning
confidence: 98%
“…Recent in vivo and in vitro analyses of the protein translocation mechanisms of Haloferax volcanii, a halophilic archaeon amenable to genetic and biochemical analyses, have complemented genomic and structural analyses of the archaea (19,35). The composition of the archaeal SRP is more similar to that of eukaryotes than the composition of bacterial SRP (10,29,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comprising an eukaryal-like SRP and a bacterial-like SRP receptor (20,21), the archaeal SRP pathway could serve to target translating ribosomes to the membrane, as in Eukarya and Bacteria. To date, archaeal SRP from several species has been reassembled from purified components (22)(23)(24) and has been isolated from H. volcanii (25), whereas binding of the archaeal SRP receptor to membrane vesicles has also been shown (26,27). Moreover, as in Eukarya (28,29) and Bacteria (30,31), recent in vitro studies have revealed that the translocon also serves as the membrane ribosomal receptor in Archaea (32).…”
mentioning
confidence: 99%